2004
DOI: 10.3748/wjg.v10.i16.2439
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of HBV and HCV by multiplex PCR normalization

Abstract: AIM:To design and establish a method of multiplex PCR normalization for simultaneously detecting HBV and HCV. METHODS:Two pairs of primers with a 20 bp joint sequence were used to amplify the target genes of HBV and HCV by two rounds of amplification. After the two rounds of amplification all the products had the joint sequence. Then the joint sequence was used as primers to finish the last amplification. Finally multiplex PCR was normalized to a single PCR system to eliminate multiplex factor interference. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…8 Wang et al demonstrated that the sensitivity of multiplex normalized PCR method was 78.6%, 75%, and 83.3% for the detection of HBV DNA, HCV RNA, and super-infection of HBV and HCV, with specificity of 80%, 90%, and 70%, respectively. 9 The superinfection rate of HBV and HCV was very high and is a leading cause of chronic hepatitis and hepatocellular carcinoma. [20][21][22] Konomi et al 23 reported a multiplex PCR method for simultaneous detection of hepatitis B, C, and G viral genomes, where the levels of concordance with the data obtained by conventional single PCR method were 100% for single infection, 98-100% for double infection, and 92% for triple infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Wang et al demonstrated that the sensitivity of multiplex normalized PCR method was 78.6%, 75%, and 83.3% for the detection of HBV DNA, HCV RNA, and super-infection of HBV and HCV, with specificity of 80%, 90%, and 70%, respectively. 9 The superinfection rate of HBV and HCV was very high and is a leading cause of chronic hepatitis and hepatocellular carcinoma. [20][21][22] Konomi et al 23 reported a multiplex PCR method for simultaneous detection of hepatitis B, C, and G viral genomes, where the levels of concordance with the data obtained by conventional single PCR method were 100% for single infection, 98-100% for double infection, and 92% for triple infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the multiplex PCR becomes a highly cost-effective method because of the reduction in labor and reagent and faster detection. [8][9][10] Multiplex PCR has been used for detection of HBV and coinfection with both HAV and HCV. 11 The present study was designed with the aim to develop a rapid, reliable, and cost-effective multiplex PCR assay for the simultaneous detection of both DNA and RNA containing hepatitis viruses which are highly prevalent in India such as HBV, HCV, and HEV.…”
mentioning
confidence: 99%
“…In contrast, none of the anti-HCV negative patients were shown to be viremic by the PCR as mention by De Albuquergue et al (2005). The detection of HCV RNA in non-hepatitis patients could be explained by the fact that the patients might be in the early stage of acute hepatitis, and the antibody had not been produced yet (Wang et al, 2004). On the other hand, one cannot exclude the existence of impaired immune responses in some of these patients (Schneeberger et al, 1998).…”
Section: Hcv Rna Prevalence In Haemodialysis Patientsmentioning
confidence: 99%
“…Possible explanations for this low percentage of viremic patients in our population include: the level of viremia may be low and below detectable level of PCR assay at time of sampling, the pattern of fluctuating viremia or intermittent viremia, patients might be cured from HCV infection at time of sampling (Bdour, 2002;Al-Kubaisy et al, 2003;and Wang et al, 2004). PCR-based methods reliability may further be compromised if viral RNA is lost in the serum or plasma through storage or improper laboratory handling or if it is absent from the circulation during sample collection (Zein, 2000).…”
Section: Hcv Rna Prevalence In Haemodialysis Patientsmentioning
confidence: 99%
“…When the virus was cleaned up, only the antibody was positive, the nucleic acids could not be detected. Hence, the detection rate of PCR was lower when ELISA was used as a golden standard (24).…”
Section: Discussionmentioning
confidence: 99%